Connecting the Forgotten/Anonymous with the Remembered/Famous: German Women Typesetters and Dr. Jose Rizal - Fernandez, Albina Peczon (Review of Women's Studies; Vol 8 No 2 (1998): Review of Women's Studies Volume VIII, Number 2 (July-December 1998))
---